Method for preparing lithium ion battery cathode material based on low-quality ternary precursor, cathode material and application thereof
Patent Information
- Application Number
- CN202610896314.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-20
AI Technical Summary
在实际生产和运输中,高镍正极前驱体Ni0.8Co0.1Mn0.1(OH)2难免与空气接触,致使表面碳酸盐化和水分子吸附,导致结构退化从而形成低品质前驱体,利用其制备的正极材料LiNi0.8Co0.1Mn0.1O的整体性能显著劣化,极易引起包括锂、镍和钴在内的关键战略金属资源的巨大浪费
本发明以空气环境下失效的低品质前驱体Ni0.8Co0.1Mn0.1(OH)2、乙酸锂和氢氧化锂为原料,并以较高的温度分两步煅烧,制备的锂离子电池正极材料具有更稳定的表面化学环境,归因于乙酸锂的引入,降低了高温锂化阶段前驱体表面因在空气中存储产生的碳酸盐污染物的熔点,使锂以液相渗透进入固相前驱体中,优化了化学嵌锂过程,实现原子级均匀固溶,从而提高了锂离子电池正极材料的结构稳定性,能够赋予锂离子电池优异的容量保持率和循环稳定性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically a method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors, the cathode materials themselves, and their applications. Background Technology
[0002] LiNi 0.8 Co 0.1 Mn 0.1 O2 is considered the most promising cathode material for lithium-ion batteries due to its high specific capacity and outstanding cost-effectiveness. However, its large-scale production and commercialization heavily rely on high-quality precursors. In actual production and transportation, high-nickel cathode precursors such as Ni... 0.8 Co 0.1 Mn 0.1 (OH)₂ inevitably comes into contact with air, leading to surface carbonation and water molecule adsorption, resulting in structural degradation and the formation of a low-quality precursor. This precursor is then used to prepare the cathode material LiNi. 0.8 Co 0.1 Mn 0.1 The overall performance of O deteriorates significantly, which can easily lead to a huge waste of key strategic metal resources, including lithium, nickel and cobalt.
[0003] Therefore, starting from the source of the synthesis process, research is being conducted on the preparation of LiNi cathode material based on low-quality precursors. 0.8 Co 0.1 Mn 0.1 The O method can reduce raw material loss and improve LiNi 0.8 Co 0.1 Mn 0.1 The properties of O2 are of great significance. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors, the cathode materials themselves, and their applications. This invention achieves the effective utilization of low-quality precursors, and the prepared lithium-ion battery cathode materials can endow lithium-ion batteries with excellent capacity retention and cycle stability.
[0005] This invention is achieved through the following technical solution: A method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors includes the following steps: Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1The molar ratio of nickel in (OH)2 is (1~1.04):(0.01~0.05):0.8. LiOH·H2O, CH3COOLi·2H2O, and Ni, a high-nickel cathode precursor that fails in air, are weighed out respectively. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2: Mix LiOH·H2O, CH3COOLi·2H2O, and Ni, a high-nickel cathode precursor that has failed in an air environment. 0.8 Co 0.1 Mn 0.1 (OH)2 is placed in a mortar and ground evenly to obtain a mixed powder; Step 3: Place the mixed powder into a tube furnace and pre-calcine it at 500~550℃ for 4 h in an oxygen atmosphere. After cooling to room temperature, grind it and place it back into the tube furnace. Sinter it at 800~850℃ for 10 h and cool it to room temperature to obtain the lithium-ion battery cathode material.
[0006] Furthermore, the lithium element in LiOH·H2O and CH3COOLi·2H2O in step 1 reacts with Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)2 is 1.05:0.8.
[0007] Furthermore, in step 1, the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)2 is 1.03:0.02:1.
[0008] Furthermore, the grinding time in both steps 2 and 3 is 20-30 minutes.
[0009] A lithium-ion battery cathode material with the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2 is characterized by secondary spherical particles formed by the accumulation of primary particles. The particle surfaces are smooth and free of adhering substances, and the primary particles have clear grain boundaries.
[0010] The application of a lithium-ion battery cathode material in a lithium-ion battery cathode sheet includes the following steps: S1. Weigh out LiNi according to a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; S2. The slurry is coated on the surface of aluminum foil, dried, and then hot-rolled to obtain the positive electrode sheet of lithium-ion battery.
[0011] Furthermore, the composite conductive agent of S1 is composed of Super P and KS6 mixed in a mass ratio of 2:3.
[0012] Furthermore, the adhesive solution of S1 is composed of PVDF and N-methylpyrrolidone mixed in a mass ratio of 4:96.
[0013] Furthermore, the drying of S2 is carried out in a vacuum oven at 80°C for 12 hours.
[0014] The present invention has the following beneficial technical effects: This invention utilizes low-quality Ni precursors that fail in air environments. 0.8 Co 0.1 Mn 0.1 Using (OH)2, lithium acetate, and lithium hydroxide as raw materials, and calcined in two steps at a high temperature, the prepared lithium-ion battery cathode material has a more stable surface chemical environment. This is attributed to the introduction of lithium acetate, which lowers the melting point of carbonate contaminants generated on the surface of the precursor during the high-temperature lithiation stage due to storage in air. This allows lithium to penetrate into the solid-phase precursor in the liquid phase, optimizing the chemical lithium intercalation process and achieving atomically uniform solid solution. This improves the structural stability of the lithium-ion battery cathode material and endows lithium-ion batteries with excellent capacity retention and cycle stability.
[0015] The lithium-ion battery assembled from the positive electrode sheet prepared in this invention achieves a maximum initial discharge capacity of 200.9 mAh·g at a current density of 0.1 C within a voltage range of 2.7 V to 4.3 V. -1 It maintains a high reversible capacity at different rates from 0.1 to 5C; after 100 cycles at a current density of 1C, the capacity retention rate reaches 86.32%. Compared with lithium-ion batteries assembled with cathode sheets prepared using low-quality precursors in existing technologies, the capacity retention rate and cycle performance of the battery are significantly improved. It provides a new solution for reducing precursor loss and developing stable, high-performance lithium-ion batteries, and has broad application prospects.
[0016] This invention mixes Super P and KS6 in a certain proportion to form a composite conductive agent. Through the complementarity of Super P and KS6 in size and morphology, compared with a single-component conductive agent, it can more fully contact and connect the active material particles, providing a smoother channel for electron transport, thereby improving the rate performance of the battery. Attached Figure Description
[0017] Figure 1XRD patterns of NCM811 prepared in Example 1 and NCM811-Air prepared in Comparative Example 1; Figure 2 SEM image of NCM811 prepared in Example 1 of this invention; Figure 3 SEM image of NCM811-Air prepared in Comparative Example 1 of this invention; Figure 4 The lithium-ion batteries assembled from the positive electrode sheets prepared in Example 1 and Comparative Example 1 of this invention are shown in the first charge-discharge curves at a current density of 0.1 C within a voltage range of 2.7 V to 4.3 V. Figure 5 The lithium-ion batteries assembled from the positive electrode sheets prepared in Example 1 and Comparative Example 1 of this invention exhibit cycle performance and discharge midpoint voltage at 1 C current density within a voltage range of 2.7 V to 4.3 V. Figure 6 The rate performance of lithium-ion batteries assembled from the positive electrode sheets prepared in Example 1 and Comparative Example 1 of this invention is shown in the voltage range of 2.7 V to 4.3 V. Detailed Implementation
[0018] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0019] Examples 1 to 5 of this invention and Comparative Example 1 use the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was stored in room temperature air with a relative humidity of 75% for 10-15 days to simulate the degradation of the precursor Ni due to improper storage during actual transportation and warehousing. 0.8 Co 0.1 Mn 0.1 (OH)2 becomes ineffective upon contact with air, and the ineffective, low-quality ternary precursor Ni is then reused. 0.8 Co 0.1 Mn 0.1 (OH)2 is used to prepare positive electrode materials for lithium-ion batteries.
[0020] Example 1 Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)₂ is 1.03:0.02:0.8. LiOH·H₂O, CH₃COOLi·2H₂O, and the precursor Ni are weighed out respectively. 0.8 Co0.1 Mn 0.1 (OH)2, for later use; Step 2, add the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was stored in room temperature air with a relative humidity of 75% for 15 days to obtain a failed high-nickel cathode precursor. Step 3: Place LiOH·H2O, CH3COOLi·2H2O and the degraded high-nickel cathode precursor into a mortar and grind for 20 minutes to obtain a mixed powder; Step 4: Place the mixed powder into a tube furnace and pre-calcine at 500°C for 4 hours in an oxygen atmosphere. Cool to room temperature, grind for 20 minutes, and then place it back into the tube furnace for sintering at 800°C for 10 hours. Cool to room temperature to obtain the lithium-ion battery cathode material with the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, denoted as NCM811; Step 5: Prepare the positive electrode sheet for the lithium-ion battery. The specific process is as follows: Step 5.1: Take Super P and KS6 at a mass ratio of 2:3 and mix them, then grind them evenly to obtain a composite conductive agent; at the same time, take PVDF and disperse it in N-methylpyrrolidone at a mass ratio of 4:96 and mix them evenly to obtain an adhesive solution. Step 5.2: Weigh out LiNi at a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; Step 5.3: Coat the slurry onto the surface of aluminum foil, dry it in a vacuum oven at 80°C for 12 hours, and then perform hot rolling treatment to obtain the positive electrode sheet for lithium-ion batteries.
[0021] Example 2 Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)₂ is 1:0.05:0.8. LiOH·H₂O, CH₃COOLi·2H₂O, and the precursor Ni are weighed out respectively. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2, add the precursor Ni 0.8 Co 0.1 Mn 0.1(OH)2 was stored in room temperature air with a relative humidity of 75% for 11 days to obtain a failed high-nickel cathode precursor. Step 3: Place LiOH·H2O, CH3COOLi·2H2O and the degraded high-nickel cathode precursor into a mortar and grind for 30 minutes to obtain a mixed powder; Step 4: Place the mixed powder into a tube furnace and pre-calcine at 550°C for 4 hours in an oxygen atmosphere. Cool to room temperature, grind for 30 minutes, and then place it back into the tube furnace for sintering at 850°C for 10 hours. Cool to room temperature to obtain the lithium-ion battery cathode material with the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, denoted as NCM811; Step 5: Prepare the positive electrode sheet for the lithium-ion battery. The specific process is as follows: Step 5.1: Take Super P and KS6 at a mass ratio of 2:3 and mix them, then grind them evenly to obtain a composite conductive agent; at the same time, take PVDF and disperse it in N-methylpyrrolidone at a mass ratio of 4:96 and mix them evenly to obtain an adhesive solution. Step 5.2: Weigh out LiNi at a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; Step 5.3: Coat the slurry onto the surface of aluminum foil, dry it in a vacuum oven at 80°C for 12 hours, and then perform hot rolling treatment to obtain the positive electrode sheet for lithium-ion batteries.
[0022] Example 3 Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)₂ is 1.02:0.03:0.8. LiOH·H₂O, CH₃COOLi·2H₂O, and the precursor Ni are weighed out respectively. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2, add the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was stored in room temperature air with a relative humidity of 75% for 13 days to obtain a failed high-nickel cathode precursor. Step 3: Place LiOH·H2O, CH3COOLi·2H2O and the degraded high-nickel cathode precursor into a mortar and grind for 25 minutes to obtain a mixed powder; Step 4: Place the mixed powder into a tube furnace and pre-calcine at 525°C for 4 hours in an oxygen atmosphere. Cool to room temperature, grind for 25 minutes, and then place it back into the tube furnace for sintering at 825°C for 10 hours. Cool to room temperature to obtain the lithium-ion battery cathode material with the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, denoted as NCM811; Step 5: Prepare the positive electrode sheet for the lithium-ion battery. The specific process is as follows: Step 5.1: Take Super P and KS6 at a mass ratio of 2:3 and mix them, then grind them evenly to obtain a composite conductive agent; at the same time, take PVDF and disperse it in N-methylpyrrolidone at a mass ratio of 4:96 and mix them evenly to obtain an adhesive solution. Step 5.2: Weigh out LiNi at a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; Step 5.3: Coat the slurry onto the surface of aluminum foil, dry it in a vacuum oven at 80°C for 12 hours, and then perform hot rolling treatment to obtain the positive electrode sheet for lithium-ion batteries.
[0023] Example 4 Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)₂ is 1.01:0.04:0.8. LiOH·H₂O, CH₃COOLi·2H₂O, and the precursor Ni are weighed out respectively. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2, add the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was stored in room temperature air with a relative humidity of 75% for 14 days to obtain a failed high-nickel cathode precursor. Step 3: Place LiOH·H2O, CH3COOLi·2H2O and the degraded high-nickel cathode precursor into a mortar and grind for 25 minutes to obtain a mixed powder; Step 4: Place the mixed powder into a tube furnace and pre-calcine at 520°C for 4 hours in an oxygen atmosphere. Cool to room temperature, grind for 30 minutes, and then place it back into the tube furnace for sintering at 815°C for 10 hours. Cool to room temperature to obtain the lithium-ion battery cathode material with the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, denoted as NCM811; Step 5: Prepare the positive electrode sheet for the lithium-ion battery. The specific process is as follows: Step 5.1: Take Super P and KS6 at a mass ratio of 2:3 and mix them, then grind them evenly to obtain a composite conductive agent; at the same time, take PVDF and disperse it in N-methylpyrrolidone at a mass ratio of 4:96 and mix them evenly to obtain an adhesive solution. Step 5.2: Weigh out LiNi at a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; Step 5.3: Coat the slurry onto the surface of aluminum foil, dry it in a vacuum oven at 80°C for 12 hours, and then perform hot rolling treatment to obtain the positive electrode sheet for lithium-ion batteries.
[0024] Example 5 Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)₂ is 1.04:0.01:0.8. LiOH·H₂O, CH₃COOLi·2H₂O, and the precursor Ni are weighed out respectively. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2, add the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was stored in room temperature air with a relative humidity of 75% for 10 days to obtain a failed high-nickel cathode precursor. Step 3: Place LiOH·H2O, CH3COOLi·2H2O and the degraded high-nickel cathode precursor into a mortar and grind for 30 minutes to obtain a mixed powder; Step 4: Place the mixed powder into a tube furnace and pre-calcine at 540°C for 4 hours in an oxygen atmosphere. Cool to room temperature, grind for 20 minutes, and then place it back into the tube furnace for sintering at 840°C for 10 hours. Cool to room temperature to obtain the lithium-ion battery cathode material with the chemical formula LiNi.0.8 Co 0.1 Mn 0.1 O2, denoted as NCM811; Step 5: Prepare the positive electrode sheet for the lithium-ion battery. The specific process is as follows: Step 5.1: Take Super P and KS6 at a mass ratio of 2:3 and mix them, then grind them evenly to obtain a composite conductive agent; at the same time, take PVDF and disperse it in N-methylpyrrolidone at a mass ratio of 4:96 and mix them evenly to obtain an adhesive solution. Step 5.2: Weigh out LiNi at a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; Step 5.3: Coat the slurry onto the surface of aluminum foil, dry it in a vacuum oven at 80°C for 12 hours, and then perform hot rolling treatment to obtain the positive electrode sheet for lithium-ion batteries.
[0025] Comparative Example 1 Step 1: Weigh out LiOH·H2O and the precursor Ni according to a lithium to nickel molar ratio of 1.05:1. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2, add the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was stored in room temperature air with a relative humidity of 75% for 15 days to obtain a failed high-nickel cathode precursor. Step 3: Place LiOH·H2O and the degraded high-nickel cathode precursor into a mortar and grind for 20 min to obtain a mixed powder; Step 4: Place the mixed powder into a tube furnace and pre-calcine at 500°C for 4 hours in an oxygen atmosphere. Cool to room temperature, grind for 20 minutes, and then place it back into the tube furnace for sintering at 800°C for 10 hours. Cool to room temperature to obtain the lithium-ion battery cathode material with the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, denoted as NCM811-Air; Step 5: Prepare the positive electrode sheet for the lithium-ion battery. The specific process is as follows: Step 5.1: Take Super P and KS6 at a mass ratio of 2:3 and mix them, then grind them evenly to obtain a composite conductive agent; at the same time, take PVDF and disperse it in N-methylpyrrolidone at a mass ratio of 4:96 and mix them evenly to obtain an adhesive solution. Step 5.2: Weigh out LiNi at a mass ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; Step 5.3: Coat the slurry onto the surface of aluminum foil, dry it in a vacuum oven at 80°C for 12 hours, and then perform hot rolling treatment to obtain the positive electrode sheet for lithium-ion batteries.
[0026] from Figure 1 It can be seen that the diffraction peaks of the lithium-ion battery cathode material NCM811 prepared in Example 1 and the lithium-ion battery cathode material NCM811-Air prepared in Comparative Example 1 are both sharp and clear, consistent with the standard XRD card of LiNiO2 (PDF#09-0063, space group R-3m), indicating that both Example 1 and Comparative Example 1 successfully prepared LiNiO2. 0.8 Co 0.1 Mn 0.1 O2 layered cathode material.
[0027] from Figure 2 It can be seen that the lithium-ion battery cathode material NCM811 prepared in Example 1 has a spherical morphology. It is a secondary spherical particle obtained by the close packing of primary particles. The particle surface is smooth and free of adhering substances, and the primary particles have clear grain boundaries.
[0028] from Figure 3 It can be seen that the lithium-ion battery cathode material NCM811-Air prepared in Comparative Example 1 has a spherical morphology. It is a secondary spherical particle obtained by the close packing of primary particles. The particle surface is rough with attached substances, and the grain boundaries of the primary particles are blurred.
[0029] The lithium-ion battery cathode sheets prepared in Example 1 and Comparative Example 1 were assembled into lithium-ion batteries, and the battery performance was tested. The results are shown in [reference needed]. Figures 4-6 In the figure: NCM811 represents a lithium-ion battery assembled from the lithium-ion battery positive electrode prepared in Example 1, and NCM811-Air represents a lithium-ion battery assembled from the lithium-ion battery positive electrode prepared in Comparative Example 1. from Figure 4 It can be seen that, within a voltage range of 2.7 V to 4.3 V and a current density of 0.1 C, the lithium-ion battery assembled from the lithium-ion battery positive electrode prepared in Example 1 has a higher initial discharge specific capacity of 200.9 mAh·g compared to the lithium-ion battery assembled from the lithium-ion battery positive electrode prepared in Comparative Example 1. -1 .
[0030] from Figure 5It can be seen that the lithium-ion battery assembled from the lithium-ion battery positive electrode sheet prepared in Comparative Example 1 retains 43.64% of its initial capacity after 100 cycles at 1C; the lithium-ion battery assembled from the lithium-ion battery positive electrode sheet prepared in Example 1 retains 86.32% of its initial capacity after 100 cycles at 1C, indicating that it has a high capacity retention rate. At the same time, the average discharge voltage of the lithium-ion battery assembled from the lithium-ion battery positive electrode sheet prepared in Comparative Example 1 drops sharply from 3.77 V to 3.29 V after 100 cycles, ΔV = 0.48 V, while the lithium-ion battery assembled from the lithium-ion battery positive electrode sheet prepared in Example 1 shows a more stable voltage curve after 100 cycles, ΔV = 0.02 V, which is significantly lower than 0.48 V, showing a slight decay. It is evident that the lithium-ion battery positive electrode material NCM811 prepared in Example 1 can endow the lithium-ion battery with good capacity retention and cycle stability.
[0031] from Figure 6 It can be seen that, compared with the lithium-ion battery assembled from the lithium-ion battery positive electrode prepared in Comparative Example 1, the lithium-ion battery assembled from the lithium-ion battery positive electrode prepared in Example 1 exhibits stronger capacity retention capability in the range of 0.1~5 C, indicating that it has better kinetic response.
Claims
1. A method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors, characterized in that, Includes the following steps: Step 1: According to the lithium element in LiOH·H2O, the lithium element in CH3COOLi·2H2O, and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)2 is (1~1.04):(0.01~0.05):0.
8. LiOH·H2O, CH3COOLi·2H2O, and Ni, a high-nickel cathode precursor that fails in air, are weighed out respectively. 0.8 Co 0.1 Mn 0.1 (OH)2, for later use; Step 2: Mix LiOH·H2O, CH3COOLi·2H2O, and Ni, a high-nickel cathode precursor that has failed in an air environment. 0.8 Co 0.1 Mn 0.1 (OH)2 is placed in a mortar and ground evenly to obtain a mixed powder; Step 3: Place the mixed powder into a tube furnace and pre-calcine it at 500~550℃ for 4 h in an oxygen atmosphere. After cooling to room temperature, grind it and place it back into the tube furnace. Sinter it at 800~850℃ for 10 h and cool it to room temperature to obtain the lithium-ion battery cathode material.
2. The method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors according to claim 1, characterized in that, In step 1, the lithium element in LiOH·H2O and CH3COOLi·2H2O reacts with Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)2 is 1.05:0.
8.
3. The method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors according to claim 1, characterized in that, The lithium elements in LiOH·H2O, CH3COOLi·2H2O, and Ni in step 1 0.8 Co 0.1 Mn 0.1 The molar ratio of nickel in (OH)2 is 1.03:0.02:0.
8.
4. The method for preparing lithium-ion battery cathode materials based on low-quality ternary precursors according to claim 1, characterized in that, The grinding time in steps 2 and 3 is 20-30 minutes.
5. A lithium-ion battery cathode material prepared by the method according to any one of claims 1 to 4, characterized in that, The chemical formula is LiNi 0.8 Co 0.1 Mn 0.1 O2 is characterized by secondary spherical particles formed by the accumulation of primary particles. The particle surfaces are smooth and free of adhering substances, and the primary particles have clear grain boundaries.
6. The application of the lithium-ion battery cathode material according to claim 5 in a lithium-ion battery cathode sheet, characterized in that it includes the following steps: S1. Weigh out LiNi according to a mass ratio of 8:1:
1. 0.8 Co 0.1 Mn 0.1 O2, composite conductive agent and binder solution are mixed and ground evenly to form a slurry; S2. The slurry is coated on the surface of aluminum foil, dried, and then hot-rolled to obtain the positive electrode sheet of lithium-ion battery.
7. The application according to claim 6, wherein the composite conductive agent of S1 is formed by mixing Super P and KS6 in a mass ratio of 2:
3.
8. The application according to claim 6, characterized in that the adhesive solution of S1 is composed of PVDF and N-methylpyrrolidone mixed in a mass ratio of 4:
96.
9. The application according to claim 6, wherein the drying of S2 is performed in a vacuum oven at 80°C for 12 hours.
